Corn stalk as starting material to prepare a novel adsorbent via SET-LRP and its adsorption performance for Pb(II) and Cu(II). Issue 3 (11th March 2020) - Wang, Yazhen; Li, Shuang; Ma, Liqun; Dong, Shaobo; Liu, Li
Abstract : Corn stalk was used as the initial material to prepare a corn stalk matrix-g-polyacrylonitrile-based adsorbent. At first, the corn stalk was treated with potassium hydroxide and nitric acid to obtain the corn stalk-based cellulose (CS), and then the CS was modified by 2-bromoisobutyrylbromide (2-BiBBr) to prepare a macroinitiator. After that, polyacrylonitrile (PAN) was grafted onto the macroinitiator by single-electron transfer living radical polymerization (SET-LRP). A novel adsorbent AO CS-g-PAN was, therefore, obtained by introducing amidoxime groups onto the CS-g-PAN with hydroxylamine hydrochloride (NH2 OH · HCl). FTIR, SEM and XPS were applied to characterize the structure of AO CS-g-PAN. The adsorbent was then employed to remove Pb(II) and Cu(II), and it exhibited a predominant adsorption performance on Pb(II) and Cu(II). The effect of parameters, such as temperature, adsorption time, pH and the initial concentration of metal ions on adsorption capacity, were examined in detail during its application. Results suggest that the maximum adsorption capacity of Pb(II) and Cu(II) was 231.84 mg g –1 and 94.72 mg g −1, and the corresponding removal efficiency was 72.03% and 63%, respectively. The pseudo-second order model was more suitable to depict the adsorption process. And the adsorption isotherm of Cu(II) accorded with the Langmuir model, while the Pb(II) conformed better to the Freundlich isotherm model.